The Relationship of Psychological Fluency with a Motivation of Achievement for Volleyball Players-Seating - Ulsattar, Maher Abd Ulelah Abd (International Journal of Psychosocial Rehabilitation, 2020)
The first topic contains the introduction of the research and its importance, which is summarized by the study variables psychological divorce and its relationship to motivation of achievement, as the adoption of the ball players sitting on the mental and psychological capabilities as much as it depends on the physical and skills, which leads to the improvement of its players, and the adoption of the results of psychological measurements of importance in the performance of the game of volleyball seating and motivation, including athletic achievement of players and measured and identify the psychological fluency of players and measured on the sample search for national team players volleyball Sit. Due to the importance of mental and psychological preparation in addition to the physical and skill preparation of the player volleyball seating and ensure access to the most accurate skill performance commensurate with the requirements of the game. Once the coach has been able to identify the initial motivation of the player towards the achievement and identify psychological fluency is the engine of his sports behavior in achieving a good result commensurate with his physical capabilities and skill, including skill overwhelming beaten by the coach of the opportunities for success and repetition of performance and acquired psychological fluency and performance in accordance with the capabilities of players In general where it is possible through this psychological divorce and promote access to achieve success that the need for psychological divorce comes at the forefront of psychological needs after physiological needs are more important than any other needThe motivation of achievement varies depending on the players in their responses to the stimuli and different positions depending on individual differences, the situation that threatens the player may be a challenge to the other player, so the second player may see an opportunity to appreciate himself and increase motivation achievement.Identify the relationship of psychological divorce and its relationship to the motivation of achievement for the players of the national team ball volleyball seating. To identify a psychological divorce and its relationship to skill overwhelming beaten the players of the national team ball. There is a correlation significant statistical significance between psychological fluency and motivation achievement. The players of the national team volleyball seatingThere is a correlation significant statistical significance between psychological fluency and its relationship to skill overwhelming beaten the players of the national team volleyball seating The second topic dealt with a set of theoretical axes that are directly related to research and its variables. And the third topic the researcher has chosen the descriptive method survey method to solve the problem of research and the sample of the research sample was chosen in a deliberate way and be the community of origin and represented by the  players national team volleyball seating the total number of players (12) for the sports season (2016-20170). The fourth section includes the presentation of the statistical results reached by the researcher,It has been achieved through the imposition of research in the presence of a statistically significant relationship between the psychological divorces. Motivation achievement players of the national team of volleyball seatingIn light of this, a number of recommendations were reached: • The measure of motivation of achievement and psychological divorce can be used by coaches periodically on the players.• give more attention to training players on psychological skills